It’s about time: Intergenerational equity and nutrition - Gillespie, Stuart (2020)
In his 2019 book “Upheaval: How Nations Cope with Crises and Change”, Jared Diamond starts by interrogating the word ‘crisis’. Coming from the Greek noun ‘krisis’ and the verb ‘krino’ there are several meanings — to separate, decide, a turning point. Crises differ in terms of the way they emerge, their scale, duration, and impact. Some come as a shock, some are slow-burn — though in reality this distinction may be blurred once we look below the surface. The COVID-19 pandemic is a sudden-onset crisis, while climate change is slow-burn (albeit linked to increasing shocks like floods and droughts). The biggest cause of global ill-health and premature mortality – malnutrition — is also slow-burn. All three crises are massive in scale, they overlap and interact, and they share many drivers. In 2019, a Lancet Commission delivered an incisive analysis of the global syndemic of obesity, undernutrition, and climate change. This was a year before the pandemic. COVID-19 has since added another crisis into this toxic mix.